Notable Figures of Sunni Sufism in Libya (Sheikh Abdul Salam Al-Asmar as Model) - Al-Shuwain, Ibrahim Ahmed; Akash, Hussain A. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This study aims to understand the meaning of Sufism, consider the opinions and sayings of some writers who explained the meaning of Sufism, and explain some of these definitions. It also aims to identify a Sufi personality who is considered a pole of Sunni Sufism in Libya, and to demonstrate the Sufi approach that he followed throughout his life, and to state his opinion on some Sufi Pretenders who distorted Sunni Sufism.